Core Values and Decision-Making for Sustainable Business An International Perspective - Verkuil, Arie Hans.; Milow, Uta.; Hinz, Andreas; Al-Kilani, Mahmoud; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access volume discusses the core values and decision-making for sustainable business in general, and includes research findings and country cases on addressing challenges. It emphasizes the importance of adapting products or services to local needs, considering cultural differences and sustainability. Some of the chapters address questions related to improving sustainability in micro, small and medium-sized enterprises (MSMEs), and cover circular economy and responsible consumption. Others look at the normative framework conditions for business development; sustainability in supply chains; the involvement of stakeholders and their influence on market presence; entrepreneurial decision-making for sustainability; and approaches to teaching international and sustainability-oriented entrepreneurship. The volume sheds light on the pivotal role MSMEs play in shaping a sustainable future and is written for researchers, practitioners, and students working on related topics. .
Transforming global challenges into opportunities for sustainable entrepreneurship -- Core values of sustainable business decision making -- Sustainability in SMEs what core values are really important -- Core Values of Sustainable Innovation in Indonesian SMEs -- Innovative Marketing Strategy for Green Products in Search of Better Customer Acquisition -- An international view on sustainable business development country studies -- The Influence of Incentive Alignment, Cost Sharing, and Responsible Action Scenario to Agriculture Supply Chain Performance in an Indonesian Study -- From Values to Practice Evaluating the Intention of Indian MSMEs to Adopt Sustainable Business Practices -- Stakeholder Involvement to Foster Sustainable Business Practices in Indonesian MSMEs -- Barriers to Business Model Innovation Insights from SMEs in Switzerland -- Integrated Approach to Internationalization in Higher Education -- Second-hand Luxury for Generations Y and Z Embracing Responsible Consumption or Hunting for Luxury Brand Treasures An Analysis from France Using the Theory of Planned Behavior -- Circular economy in practice the benefits of collaboration for securing material flow in a US study -- Final thoughts Entrepreneurship challenges in a demanding political and economic ecosystem.
Keywords: Strategic planning; Leadership; Positive psychology; Psychology, Industrial; Sustainability; Business Strategy and Leadership; Positive Psychology; Leadership Psychology; Sustainability